Immunogenicity of Pneumococcal Polysaccharide Vaccine in patients with rheumatoid arthritis - B. Ts. Batozhargalova; N. A. Sagatbayeva; G. M. Abdullayeva; Sh. K. Bytyrkhanov; I. L. Solovеva; M. P. Kostinov; A. D. Shmitko (Журнал инфектологии)
The presented review searched for articles in the databases PubMed, Web of Science, Scopus, Google Scholar, eLibrary (2002-2022) and assessed the immunogenicity of the 23-valent polysaccharide pneumococcal vaccine (PPV23) in adult patients with rheumatoid arthritis (RA), receiving various antirheumatic drugs. The results of this review indicated sufficient immunogenicity of PPV23 in RA patients receiving monotherapy with various biological drugs (bDMARDs) (TNFα inhibitors, IL6 receptor inhibitors, T-lymphocyte costimulation blockers), targeted synthetic disease-modifying antirheumatic drugs (tsDMARDs), and glucocorticoids (GC) in medium and low doses. Monotherapy with methotrexate (MTX), rituximab and combination therapy with bDMARDs +MTX, tsDMARDs+MTX in RA patients reduced the postvaccination pneumococcal response. IgG AT generated in response to PPV23 injection shown functional activity even in RA patients whose antibodies were either lowered in patients receiving MTX or were not detectable at protective values following bDMARD therapy. The potential for pneumococcus antibody production in RA patients receiving therapy with disease-modifying antirheumatic drugs (DMARDs), tsDMARDs and bDMARDs, was concluded. Vaccination against pneumococcal infection should be advised prior to starting therapy due to the likelihood of low antibody levels developing during rituximab treatment.